Heterogeneous acidic catalysts for the tetrahydropyranylation of alcohols and phenols in green ethereal solvents - Azzena, Ugo; Carraro, Massimo; Modugno, Gloria; Pisano, Luisa; Urtis, Luigi (Beilstein Journal of Organic Chemistry, 2018)
The application of heterogeneous catalysis and green solvents to the set up of widely employed reactions is a challenge in contemporary organic chemistry. We applied such an approach to the synthesis and further conversion of tetrahydropyranyl ethers, an important class of compounds widely employed in multistep syntheses. Several alcohols and phenols were almost quantitatively converted into the corresponding tetrahydropyranyl ethers in cyclopentyl methyl ether or 2-methyltetrahydrofuran employing NH4HSO4 supported on SiO2 as a recyclable acidic catalyst. Easy work up of the reaction mixtures and the versatility of the solvents allowed further conversion of the reaction products under one-pot reaction conditions.
Keywords: green chemistry; green solvents; heterogeneous catalysts; multistep reactions; tetrahydropyranylation